2006
DOI: 10.1002/bjs.5398
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of local gentamicin–collagen treatment in advancement flap repair for anal fistula

Abstract: Endoanal advancement flap repair for anal fistula has a fairly high primary recurrence rate. Healing was not significantly improved by local application of gentamicin-collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 20 publications
0
33
1
8
Order By: Relevance
“…Bu yöntemlerden bazıları bioprostetik tıkaçlar, anorektal doku flebleri gibi yöntemlerdir. 24,25,26 Ancak bu yöntemler doku iyileşmesini ve fistülün kapanması üzerine istenilen sonuçları verememiş ve fistülün tekrarlamasına engel olamamıştır. Bizim çalışmamızda FiLaC TM lazer radyal uçlu fiber tarafından fistül yoluna gönderilen lazer enerjisi, endolüminal granülasyon dokusunu ve fistül yolunun epitelyal duvarını tahrip eder.…”
Section: Discussionunclassified
“…Bu yöntemlerden bazıları bioprostetik tıkaçlar, anorektal doku flebleri gibi yöntemlerdir. 24,25,26 Ancak bu yöntemler doku iyileşmesini ve fistülün kapanması üzerine istenilen sonuçları verememiş ve fistülün tekrarlamasına engel olamamıştır. Bizim çalışmamızda FiLaC TM lazer radyal uçlu fiber tarafından fistül yoluna gönderilen lazer enerjisi, endolüminal granülasyon dokusunu ve fistül yolunun epitelyal duvarını tahrip eder.…”
Section: Discussionunclassified
“…In case of a repair of an anal fistula, using advancement flap gentamicin-collagen did not decrease the infection rate, nor was a different reccurence rate observed [17].…”
Section: Discussionmentioning
confidence: 84%
“…Collagen matrix is fully biodegradable and resorbed within 1 to 8 weeks, depending on the vascularization of the tissue [15,17]. In contrast, micro-dispersed oxidised cellulose is fully resorbed within the first 48 hours in 94 % of wounds.…”
Section: Discussionmentioning
confidence: 99%
“…In studies that have shown a difference in healing rates with age, increased age is associated with a higher likelihood of healing. Gustafsson et al found a trend toward a higher likelihood of healing with age greater than 50 [ 28 ]. Similarly, healing rates were 45.7 % for age less than 40, 67.9 % for those aged 40-60, and 100 % for those older than 60 in a paper by Sonoda et al [ 29 ].…”
Section: Effect Of Other Factors On Healing Rates Patient Characterismentioning
confidence: 90%